2003
DOI: 10.3748/wjg.v9.i2.291
|View full text |Cite
|
Sign up to set email alerts
|

HCV replication in PBMC and its influence on interferon therapy

Abstract: HCV is capable of infecting and replicating in PBMCs, and HCVNS5 protein was expressed in PBMCs. The patients with minus strand HCV RNA in PBMCs showed a significantly lower 6-month sustained response to IFN, suggesting that minus-strand HCV RNA in PBMCs may be one of the factors influencing response to IFN therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 34 publications
6
34
0
1
Order By: Relevance
“…Interestingly, patients with detectable negative-strand HCV RNA in PBMCs had lower interferon (IFN) sustained response rates compared to those without detectable negative-strand HCV RNA in PBMCs. 103 Thus, it is provocative to speculate that low-level replication of HCV in PBMCs may lead to reactivation of HCV after termination of therapy and/or predict response to therapy. 80,99,100,[102][103][104][105] As reviewed elsewhere, HCV is likely involved in several neurologic syndromes.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, patients with detectable negative-strand HCV RNA in PBMCs had lower interferon (IFN) sustained response rates compared to those without detectable negative-strand HCV RNA in PBMCs. 103 Thus, it is provocative to speculate that low-level replication of HCV in PBMCs may lead to reactivation of HCV after termination of therapy and/or predict response to therapy. 80,99,100,[102][103][104][105] As reviewed elsewhere, HCV is likely involved in several neurologic syndromes.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%
“…103 Thus, it is provocative to speculate that low-level replication of HCV in PBMCs may lead to reactivation of HCV after termination of therapy and/or predict response to therapy. 80,99,100,[102][103][104][105] As reviewed elsewhere, HCV is likely involved in several neurologic syndromes. 16 While central nervous system (CNS) involvement is less frequent, the detection of negative-strand HCV RNA in the CNS 29 suggests a potential link between HCV and these extrahepatic pathol- ogies.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%
“…These include mixed cryoglobulinemia, non-Hodgkin's lymphoma, cutaneous vasculitis, membranoproliferative glomerulonephritis, neuropathy, lymphoproliferative disorders, porphyria cutanea tarda, lichen planus, and Sjogren's syndrome (1, 7). HCV is reported to replicate in extrahepatic sites like interstitial cells of the kidney, acinar cells of the pancreas, peripheral blood mononuclear cells, and mononuclear cells of lymph nodes (5,14). Currently, the diagnosis of HCV infection is achieved by the detection of HCV RNA in plasma or serum.…”
mentioning
confidence: 99%
“…HCV genotype and the baseline level of viremia have been pointed out as the most important predictive factors of responsiveness to IFN therapy [22] . However, several studies suggested that other factors, such as the heterogeneity of virus population [23] and replication in PBMC [24] , might also influence the effectiveness of therapy. Like most RNA viruses, HCV circulates in the human host as a complex population of different but closely related viral variants, commonly referred to as quasispecies [25] .…”
Section: Discussionmentioning
confidence: 99%